"The Double Dividend of Training" - Labor Market Effects of Work-Related Continuous Education in Switzerland - Stefan Denzler; Jens Ruhose; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper presents the first longitudinal estimates of the effect of work-related training on labor market outcomes in Switzerland. Using a novel dataset that links official census data on adult education to longitudinal register data on labor market outcomes, we apply a regression-adjusted matched difference-in-differences approach with entropy balancing to account for selection bias and sorting on gains. We find that training participation increases yearly earnings and reduces the risk of unemployment two years after the treatment. However, the effects are heterogeneous as to gender, age, education, and regional labor market context. The gains are highest for middle-aged men with formal vocational education working in either depressed or booming labor markets.
Keywords: I21; I26; J24; M53; 330; continuous education; wages; unemployment; entropy balancing; Switzerland